2019
DOI: 10.1097/corr.0000000000000652
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Correct Congenital Spinal Deformity Associated With a Tethered Cord Without Prophylactic Intradural Detethering?

Abstract: Background Patients who have a congenital spinal deformity with a tethered cord generally are treated with prophylactic intradural detethering before deformity correction. However, the detethering procedure carries substantial risk, and it is not clear whether deformity correction can be performed without detethering. Questions/purposes To determine the (1) correction rate, (2) proportion of patients who experienced complications after surgery, and (3) neurological status after recovery from surgery in a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the current study, Tao and colleagues [3] have shown that, in carefully selected patients, scoliosis correction can be surgically obtained without incurring neurologic injury even in the absence of detethering prior to correction. Their series of 41 patients without permanent neurologic injury does not however, prove that scoliosis correction without detethering is "safe."…”
mentioning
confidence: 59%
“…In the current study, Tao and colleagues [3] have shown that, in carefully selected patients, scoliosis correction can be surgically obtained without incurring neurologic injury even in the absence of detethering prior to correction. Their series of 41 patients without permanent neurologic injury does not however, prove that scoliosis correction without detethering is "safe."…”
mentioning
confidence: 59%
“…[ 2 , 4 , 5 , 26 ] An additional nine articles were included, describing spinal deformity correction in patients with congenital scoliosis with intraspinal pathology, such as diastematomyelia, tethered cord, and syringomyelia with or without Chiari malformation [ Table 3 ]. [ 1 , 3 , 8 , 11 , 19 - 21 , 23 , 27 ]…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nine articles described the use of osteotomies or posterior vertebral column resection to correct kyphoscoliotic deformities without lengthening the spinal column. [ 1 , 2 , 8 , 11 , 19 , 20 , 23 , 26 , 27 ] Of all the articles reviewed, seven described the use of compressive forces on the convex side of the deformity as the primary mode of correction. [ 5 , 12 , 27 ]…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17 ] Tao et al reviewed 41 patients with congenital spinal deformity and tethered cord and concluded that it was possible to correct congenital spinal deformity associated with tethered cord without prophylactic intradural detethering. [ 18 ] Nonetheless, according to the literature, only 1 or 2 specific intraspinal anomalies are typically assessed. Theoretically, concurrent multiple intraspinal anomalies (coexistence of 3 or more intraspinal anomalies including syringomyelia, split cord malformation [SCM], tethered cord, low conus, intraspinal mass, Chiari malformation or/and arachnoid cyst) can increase the risk of neurologic injury during surgical correction in CS patients compared with the normal intraspinal condition or CS patients with 1 or 2 intraspinal anomalies due to the presence of more complex intraspinal pathologies.…”
Section: Introductionmentioning
confidence: 99%